Venomous animal attacks in Pará: Correlation between deaths and serotherapy in the context of urgent and emergency care (Research, Society and Development, 2024)
Attacks by venomous animals are a major problem for public health, especially in predominantly rural regions, which are more likely to contain a greater number of these animals. Thus, effective protocols are needed in the event of attacks by venomous animals, since serotherapy is the most indicated treatment and serums need to be available when these victims are attended to. The following study aims to analyze whether there is a relationship between the evolution of the case, the use of serotherapy and the time between the bite and care for patients attacked by venomous animals in the state of Pará. This is a quantitative, analytical, observational and cross-sectional study, which used data on attacks by venomous animals from 2013 to 2022 in the state of Pará collected from the Department of Informatics of the Unified Health System (DATASUS). It was found that the best prognoses were among patients who sought medical attention with the use of serotherapy between 1 and 3 hours after the bite, progressing to total cure, while those who sought care 6 hours after the bite had higher death rates. In addition, despite the irregularity of the cases in the period analyzed, the factor of time taken to receive care after the bite, together with the use of serotherapy, represented better prognoses, with total cure rates of approximately 84% with the ideal response time being 1 hour after the attack.